DQR quo vadis? - Mölls, Johanna [Verfasser] (My University, 2022)
“Ten years ago, the Federal Government, the federal states and the social partners reached agreement on a joint position for the implementation of a German Qualifications Framework (DQR) that would establish equivalence between academic and vocational training for the first time. This article sheds light on this agreement and describes the momentum and impacts which the DQR has unfurled at a national level to date. It concludes by exploring the benefits which would accrue if a firm legal framework were established.” (BIBB-Doku)
Keywords: S 2.2.4 Anrechnung, Prüfung & Zertifizierung; 370; Deutscher Qualifikationsrahmen; Historische Entwicklung; Rechtliche Regelungen; Gleichwertigkeit